Le modèle du « bon malade » entre traités religieux et traités médicaux au xviie siècle - Cécile Floury-Buchalin (Chrétiens et Sociétés, 2013)
Following the model of the « good death », a model of the « good patient» appeared in the context of the Counter-Reformation in religious, but also literary and medical texts of the 17th century. This normative model relies on the close supervision of the patient’s state of mind and on the moral and religious reading of his sufferings. This vision often concurs with medical interpretation. In these two registers, the patient’s corruption and guilt go hand in hand with his necessary humility. The acceptance of the sufferings, whether they are sent by God or inflicted by the doctor or the surgeon, is the only way for the ones who must first think about saving their soul before wanting to comfort their body. By the reminder of the indignity of the terrestrial condition, the model of the « good patient » can go as far as forgetting or even despising the body. But if body cares must come in the second place, they are nonetheless legitimate. Indeed, the remedies as well as the illnesses are also the products of divine grace and the body is not just a carnal cell, it is also a temple of the Holy Spirit. At the patient’s bedside, spiritual caring and medical cares are to be seen as mirror images. The resistance of those who suffer is recalled here and there by subtle discordances in a set of common references and terms they draw from.